Disinterested Love. - Woodward, G. M. (George Moutard), ca. 1760-1809 (Holland, William, 1790)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Love poetry; Ireland -- Social life and customs -- 18th century; Irish -- Caricatures and cartoons